A new species of Mysidopsis (Crustacea, Mysida) from the Canary and Cape Verde archipelagos - Karl J. Wittmann (Biodiversity Data Journal)
Within the subfamily Leptomysinae (fam. Mysidae), the tribe Mysidopsini has five here acknowledged genera and 74 extant species. It embraces the genera Americamysis with six species from the coasts of the NW-Atlantic (Narragansett Bay to Florida), the Caribbean and Gulf of Mexico; Brasilomysis with two species from the SW-Atlantic off Brazilian shores and from the Pacific coast of Ecuador; Cubanomysis with three species from the Caribbean, Gulf of California and southern California; Metamysidopsis with ten species from the Atlantic coasts of the USA to Brazil, Caribbean, Gulf of Mexico and E-Pacific from California to Panama; and, finally, the globally occurring Mysidopsis. Not counting the below-described new species and one fossil species, the latter genus comprises 53 extant species and one non-nominotypical subspecies. With regard to the great number of species, this genus is comparatively homogeneous, not considering the monotypic subgenera Pseudomysidopsis and Mysidopsoides.Mysidopsis canariensis sp. nov. is described from five islands of the Canaries and two islands of the Cape Verdes (NE-Atlantic). Records are from depths of 5 to 30 m, mainly over sand, also on stones and rock. It differs from the remaining NE-Atlantic and Mediterranean congeners amongst other features by the lateral margins of the telson distally having a longer bare portion. Amongst these species, it differs from its northern vicariants M. iluroensis and M. gibbosa in addition by fewer spines on the endopod of uropods. In-situ-photos of M. canariensis sp. nov. document at least six strongly different colour variants, four of which are strikingly similar to corresponding variants of M. jenseni from the NE-Pacific coast. The latter differs from all species of the E-Atlantic, including the new one, by a mid-dorsal lappet near the caudal margin of the female carapace. A key to the species of Mysidopsis from the E-Atlantic and Mediterranean is given.